1. Diplomasi Indonesia dalam Pembebasan Sandera di Luar Negeri Studi Kasus: Diplomasi Total dalam Pembebasan WNI Sandera Abu Sayyaf pada Maret-April 2016 - Istikharoh, Annis; Putranti, Ika Riswanti; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to explain the reasons behind Indonesia’s total diplomacy strategy to release hostages under Abu Sayyaf Group. The Abu Sayyaf Group kidnapped 14 Indonesian ship crews on March and April 2016, while was passing through the Sulu Sea. Qualitative research with the explanative method is used to explain the correlation between variables. This research uses Interdependence Liberalism as analytical tool, which states that transnational actor is more significant than military force. The result indicates that there are four underlying reasons on why Indonesian Government employs total diplomacy to release the hostages from Abu Sayyaf Group. First, Indonesia was a dialogue partner for MNLF and Philippine Government in the case of the peace agreement; Second, there is trade cooperation between South Philippine and Indonesia; Third, Indonesia has global network; and fourth, soft power is being chosen / prioritized to protect the hostages.